2019
DOI: 10.15740/has/ajhs/14.2/309-312
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood opportunities of small and marginal farm families in Haryana state

Abstract: India is facing now-a-days is achieving inclusive growth and proper strategy to revive Indian agriculture. The farm population has been waiting patiently year after year for a 'new deal' for agriculture. Doubling agricultural growth is the immediate challenge. However, the package of the recent strategy and efforts seems to be incremental, rather than a holistic for reviving agriculture. Present study was conducted in Gurgaon division of Haryana state and two districts from Gurgaon division i.e. Rewari and Mah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
6
1
0
Order By: Relevance
“…AMEU (2016) revealed that respondents relied in super market for purchase of food. The findings of Jodha (2018) were in line with the findings of present study (Table 1).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…AMEU (2016) revealed that respondents relied in super market for purchase of food. The findings of Jodha (2018) were in line with the findings of present study (Table 1).…”
Section: Resultssupporting
confidence: 92%
“…Similar findings were reported by Adekoya (2009) that vegetable being most affordable food item and easily accessible consumed by 90.00 per cent of respondents. Similar findings were reported by Jodha (2018) that it was consumed by 54.33 per cent of the households. To meet food security and nutritional requirements of the family, food intake must be from different food groups.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with the one obtained in the study of Ferrao et al, (2018), where it was found the prevalence of underweight and obesity was small. The present findings are also in line with Jethi et al, (2018) and Jodha & Dahiya (2019).…”
Section: Status Of Body Mass Index (Bmi) Of Rural Householdssupporting
confidence: 94%
“…It is clear from the data that the dietary intake of women had low as majority of them been food consumption of two meals a day. The findings are in line with Jodha et al, (2019) & Gupta et al, (2020.…”
Section: Food Consumption Pattern Of Rural Householdssupporting
confidence: 86%